2020
DOI: 10.7759/cureus.11019
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fasting Lipid Profile in Patients With Chronic Liver Disease: A Descriptive Cross-Sectional Study in Tertiary Care Hospital

Abstract: Introduction: Chronic liver disease (CLD) is a term used to describe a wide spectrum of disorders, including idiopathic, infectious, genetic, drug-induced, toxin-induced, and autoimmune disorders. The common consequence of chronic damage to the liver is cirrhosis. Cirrhotic patients are further classified by their severity based on the Child-Pugh scoring system. Currently, Child-Pugh scoring consists of ascites, hepatic encephalopathy (HE), prothrombin time, serum albumin level, and total bilirubin level. Lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
(49 reference statements)
2
12
0
Order By: Relevance
“…This was supported by many previous studies and in their studies, they showed that the amount of decrement in the serum LDL was significant with increasing severity of liver damage. 10,12,13,15 The level of serum HDL in this study, was significantly decreased in cases of CLD when compared to control (p<0.001) and inversely co-related with severity of liver damage, were consistent with some of publications on this subject. 12,15 The serum triglyceride levels were significantly lower in cases of CLD than in control group (p= 0.047).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This was supported by many previous studies and in their studies, they showed that the amount of decrement in the serum LDL was significant with increasing severity of liver damage. 10,12,13,15 The level of serum HDL in this study, was significantly decreased in cases of CLD when compared to control (p<0.001) and inversely co-related with severity of liver damage, were consistent with some of publications on this subject. 12,15 The serum triglyceride levels were significantly lower in cases of CLD than in control group (p= 0.047).…”
Section: Discussionsupporting
confidence: 90%
“…This observation was supported by some reports. [10][11][12][13][14] The probable explanation for the reduced serum total cholesterol was due to the decline in synthetic function and altered metabolism. 12 Further comparison of the total cholesterol values in different Child Pugh and MELD scores showed a direct relation between the severity of liver damage and reduction in the cholesterol and this was supported by few previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several hepatic disorders in which normal liver tissue is replaced by fibrotic tissue are collectively termed chronic liver disease (CLD) [1]. Several metabolic abnormalities are common in CLD like dyslipidemias, 1 2 3 3 4 5 6 7 8 9 clotting factor deficiencies, and in some cases venous thromboembolism due to deficiency of anticoagulation factors [2].…”
Section: Introductionmentioning
confidence: 99%
“…Low energy intake and poor nutritional status facilitate the development of hepatic encephalopathy, which is associated with poor prognosis in patients with cirrhosis [ 24 ]. Therefore, avoiding long-term fasting with the intake of carbohydrates 4 h prior to anesthesia may have beneficial effects on ameliorating malnutrition in patients with cirrhosis; however, further research is warranted [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%